Investigation of the role of individual's gender in the design of graphical user interface for mobile learning device - Ling, Thong Chee; Alam, Taqbir; Amir Hussin, Amir 'Aatieff (Institute of Physics Publishing, 2020)
Nowadays, the mobile phones are making life easier which can do almost anything. Although the concept of mobile learning is not new, there are still studies undergoing about improvement so that users can study using their mobile phones. This project was a study of Graphical User Interface of m-learning applications. The study aimed to investigate whether different genders have different User Interface preferences when came to learn on mobile phones. This project conducted surveys to understand the patterns of User Interface that the users preferred for mobile learning application. The responses had pointed in develop an application based on the survey results which was a unified User Interface design preferred by both males and females. After the application development have been completed, another survey was conducted to evaluate whether the preferred User Interface designs on the application was satisfying them or not. The reviews were mostly positive and thus, a concept or theory of User Interface customization was derived from this project.